Azomethine Ylide: An Isolable 1,5-Dipole for Affecting [5+2] Cycloaddition Reactions - Yoo, Eun Jeong (Synlett, 2015)
It was recently found that 1-sulfonyl-1,2,3-triazole can act as a 1,3-dipole in the presence of rhodium(II), leading to emergence of diverse rhodium(II)-catalyzed [3+n] cycloaddition reactions using 1-sulfonyl-1,2,3-triazole. Herein, we highlight development of another dipole, azomethine ylide, which was prepared from 1-sulfonyl-1,2,3-triazole with amide and pyridine derivatives, respectively. Notably, the rhodium(II)-catalyzed reaction of 1-sulfonyl-1,2,3-triazole with pyridines resulted in generation of uniquely isolable azomethine ylide. This azomethine ylide is the first example of an isolable 1,5-dipole that could be cyclized with 2π-dipolarophiles. The new 1,5-dipole provides an avenue for the development of new organic syntheses.1 Introduction2 Reactions of 1-Sulfonyl-1,2,3-triazole with Aldehyde3 1-Sulfonyl-1,2,3-triazole as a Precursor of Azomethine Ylide4 Generation of Free Azomethine Ylide5 Outlook
Keywords: metal catalysis; diazo compound; azomethine ylide; dipolar cycloaddition; multicomponent reaction